Pembelajaran Terpadu Model Sequenced di Sekolah Dasar - Yuningsih, Imas; Adelia, Fitri; Latip, Asep Ediana (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Subject-integrated learning, which incorporates knowledge from various disciplines into one form, is one part of the independent study program. Thematic learning is defined as learning in which themes are used to integrate multiple subjects in order to provide students with meaningful experiences. The research method employed is literature review, which makes use of primary sources such as journal articles and books.